2008
DOI: 10.1063/1.2978209
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, structural, and chemical properties of HfO2 films formed by electron beam evaporation

Abstract: High dielectric constant hafnium oxide films were formed by electron beam ͑e-beam͒ evaporation on HF last terminated silicon ͑100͒ wafers. We report on the influence of low energy argon plasma ͑ϳ70 eV͒ and oxygen flow rate on the electrical, chemical, and structural properties of metal-insulator-silicon structures incorporating these e-beam deposited HfO 2 films. The use of the film-densifying low energy argon plasma during the deposition results in an increase in the equivalent oxide thickness ͑EOT͒ values. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 32 publications
6
27
0
Order By: Relevance
“…The C ox values are based on oxide thickness values obtained from high-resolution cross-sectional transmission electron microscopy (HR-TEM), taking into account any interfacial oxide layers formed in the MOS structure. The following dielectric constant values were adopted, HfO 2 (21), 28 Al 2 O 3 (8.6), 23 and the native oxide of In 0.53 Ga 0.47 As (9). 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…The C ox values are based on oxide thickness values obtained from high-resolution cross-sectional transmission electron microscopy (HR-TEM), taking into account any interfacial oxide layers formed in the MOS structure. The following dielectric constant values were adopted, HfO 2 (21), 28 Al 2 O 3 (8.6), 23 and the native oxide of In 0.53 Ga 0.47 As (9). 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…Most metallic films are prepared by costly vacuum-based deposition processes, such as chemical vapor deposition [2,3], thermal or electron beam evaporation [4], and molecular beam epitaxy [5], which usually require costly and sophisticated equipment with limited throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HfO 2 films with the cubic and/or the tetragonal crystal structure are widely used as high-k dielectric layers in field effect transistors. 5 In film form, HfO 2 can be deposited by a variety of techniques, including atomic layer deposition, 6 electron beam evaporation, 7 radio frequency, [8][9][10][11][12] direct current, [13][14][15] pulsed 16 and high pressure 17 magnetron sputtering, molecular beam epitaxy, 18 and pulse laser deposition. 2,3 With all these techniques, growth at room temperature commonly results in the formation of the m-HfO 2 phase 10,12,16,17,19,20 or amorphous films.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 With all these techniques, growth at room temperature commonly results in the formation of the m-HfO 2 phase 10,12,16,17,19,20 or amorphous films. 2,3,[5][6][7][8]13,15 Therefore, considerable research effort has been focused on the room temperature growth of the t-and the c-HfO 2 phases. A number of studies have shown that the alloying of the metal sublattice of HfO 2 by Y ͑Ref.…”
Section: Introductionmentioning
confidence: 99%